Genomic consequences of artificial selection during early domestication of a wood fibre crop. Issue 5 (2nd July 2022) - Mostert‐O'Neill, Marja M.; Tate, Hannah; Reynolds, S. Melissa; Mphahlele, Makobatjatji M.; van den Berg, Gert; Verryn, Steve D.; Acosta, Juan J.; Borevitz, Justin O.; Myburg, Alexander A.
Summary: From its origins in Australia, Eucalyptus grandis has spread to every continent, except Antarctica, as a wood crop. It has been cultivated and bred for over 100 yr in places such as South Africa. Unlike most annual crops and fruit trees, domestication of E. grandis is still in its infancy, representing a unique opportunity to interrogate the genomic consequences of artificial selection early in the domestication process. To determine how a century of artificial selection has changed the genome of E. grandis, we generated single nucleotide polymorphism genotypes for 1080 individuals from three advanced South African breeding programmes using the EUChip60K chip, and investigated population structure and genome‐wide differentiation patterns relative to wild progenitors. Breeding and wild populations appeared genetically distinct. We found genomic evidence of evolutionary processes known to have occurred in other plant domesticates, including interspecific introgression and intraspecific infusion from wild material. Furthermore, we found genomic regions with increased linkage disequilibrium and genetic differentiation, putatively representing early soft sweeps of selection. This is, to our knowledge, the first study of genomic signatures of domestication in a timber species looking beyond the first few generations of cultivation. Our findings highlight the importance of intra‐ and interspecific hybridization during early domestication.